Impact of Gentle Touch Stimulation Combined with Advanced Sensory Stimulation in Patients in a Minimally Conscious State: A Quasi-Randomized Clinical Trial - Mirjam Bonanno; Antonio Gangemi; Rosa Angela Fabio; Marco Tramontano; Maria Grazia Maggio; Federica Impellizzeri; Alfredo Manuli; Daniele Tripoli; Angelo Quartarone; Rosaria De Luca; Rocco Salvatore Calabrò (Life)
Touch, particularly affective touch mediated by C-tactile fibers, plays a key role in emotional regulation and therapeutic interventions. However, tactile stimulation is underutilized in sensory stimulation (SS) protocols for brain injury patients, despite its potential to enhance consciousness and promote recovery through neural and autonomic regulation. Tools like the Neurowave enable advanced multisensory stimulation, including audio-visual and emotional inputs, but lack tactile components. Integrating gentle touch stimulation with such systems could further enhance neuroplasticity, improve heart rate regulation, and support recovery in patients with disorders of consciousness. In this study, twenty patients affected by minimally conscious state (MCS) were divided into two groups: an experimental group (EG n.10) and a control group (CG n.10). Both groups underwent standard neurorehabilitation, including conventional physiotherapy and speech therapy. The key difference was in the type of sensory stimulation. The EG received advanced sensory stimulation with the Neurowave system (which provides audio-visual and emotional sensory stimulation) in addition to gentle touch stimulation. The CG received conventional sensory stimulation without the Neurowave and neutral gentle touch stimulation. Each patient was evaluated by a multidisciplinary rehabilitation team, using clinical scales such as coma recovery scale—revised (CSR-R), level of cognitive functioning (LCF), before (T0) and after (T1) treatment. Additionally, heart rate (HR) and neurophysiological outcomes (P300) were also recorded for both groups (EG and CG). The MANOVA model revealed a significant interaction effect between group and phase on P300 latency (F (1, 18) = 10.23, p < 0.001, η2 = 0.09), indicating that the intervention involving gentle touch stimulation significantly influenced the P300 latency in the EG. The findings of this study contribute to our understanding of the therapeutic potential of emotional multisensory stimulation, which also includes gentle touch stimulation, in MCS rehabilitation. By demonstrating significant effects on both neurophysiological and functional measures, our results support the integration of tactile interventions into comprehensive neurorehabilitation programs.